Re-Imagining Child Welfare With Service Users: What Children's Social Workers Need to be Taught in School - Terry, Samantha (My University, 2017)
As social workers we understand that service users are the most impacted stakeholders involved in service delivery models at various agencies. When it comes to the field of child welfare, there are added barriers and complications that impact a worker’s ability to develop relationships with service users. What do child welfare service users consider to be “good” social work practice, and what do they expect from their workers? This thesis will focus on the voices of those who have been most impacted by the system: those who are or have been in the care of a child welfare system. At McMaster University, a program is being initiated in partnership between the School of Social Work and various local Children’s Aid Societies in Hamilton and the surrounding areas, which will explore how child welfare service users can be incorporated into the education of social work students who plan to work in the field of child welfare. This thesis will explore what individuals who are or have been youth in the care of an Ontario Children’s Aid Society want to teach the students of this program before they become child welfare social workers. This expert feedback will then be incorporated into the curriculum of McMaster’s program, entitled: “Preparing for Critical Practice in Child Welfare” (PCPCW), which will be carried into practice by the students who graduate from the program to become child welfare social workers.
Keywords: thesis, child welfare, service users, social work education, McMaster, Canada